Feasibility, acceptability, and effects of a self-stigma reduction pilot program for Japanese individuals with type 2 diabetes - Asuka Kato; Kazuhiro Yoshiuchi; Hideki Hashimoto; Ryo Suzuki; Toshimasa Yamauchi; Takashi Kadowaki (Elsevier, 2023)
Objective: To examine the feasibility, acceptability, and effects of a self-stigma reduction program for patients with type 2 diabetes mellitus11 T2DM: type 2 diabetes mellitus. (T2DM). Methods: We adopted a within-subjects pre-post study design, measuring self-stigma among T2DM patients who received treatment at a tertiary-level hospital. Results: Of the 17 participants, 11 participants completed the program (mean age: 54.36 ± 8.58 years; women: 63.6%; mean T2DM duration: 12.09 ± 10.41 years). Participants experienced reduced levels of self-stigma between the pre- and post-study time points (mean pre-study score: 35.82 ± 16.26; mean post-study score: 25.55 ± 16.91). The difference in self-stigma was not significant (effect size: d = 0.8, χ2 = 3.6, p = 0.057). Overall, participants who completed the program were satisfied except for the duration of each session. Conclusion: The self-stigma reduction program was relatively feasible and acceptable. Although due to the small sample size our results were not statistically significant, a large reduction of self-stigma was found in those who completed the program, which is promising. Future studies with larger sample sizes are needed to measure the program's long-term effects on the reduction of self-stigma. Innovation: This program is innovative as the researchers and healthcare professionals collaborated with patients who contributed their narratives.